A comparative study on the properties of the mortar with the cathode ray tube funnel glass sand at different treatment methods. (1st September 2017) - Zhao, Hui; Poon, Chi Sun
Graphical abstract: With the rapid development of the electronic industry, the management of cathode ray tube (CRT) glass waste has become a major environmental problem. The CRT funnel glass reutilized as the replacement of river sand in the mortar is an environmental friendly management option for the CRT funnel glass waste. In this study, the CRT funnel glass sand of two treatment methods, i.e. untreated with nitric acid (n-TFG), treated with nitric acid (TFG), was used. The properties of the mortars with n-TFG, TFG glass sand were studied and compared. The mortars with TFG glass sand exhibits worse the fresh and mechanical properties than those with n-TFG glass sand. The use of TFG glass sand results in a lower drying shrinkage, alkali-silica reaction (ASR) expansion and leaching content of lead than the n-TFG glass sand series mortars. At the drying shrinkage period of 56 days, the drying shrinkage values of the mortars with TFG glass sand are within the limit of 0.075%. The ASR expansion values of the mortars prepared by TFG glass sand are below permissible limits (0.10%) at 14 days tested age. The lead leaching from the TFG glass sand series mortars comply with the regulatory limits. Highlights: Utilizing n-TFG, TFG glass sand increase the fresh, mechanical, durability properties of the mortar. n-TFG glass sand series mortar have a better fresh properties than TFG glass sand series mortar. The mortars with TFG glass sand have lower mechanical properties than those with n-TFG glass sand. The lower drying shrinkage, ASR expansion, the leaching of lead can be found in TFG glass sand mortars. Abstract: With the rapid advances of the electronic industry, the management of the cathode ray tube (CRT) glass waste has become a major environmental problem. In this study, the CRT funnel glass sand untreated with nitric acid (n-TFG) and treated with nitric acid (TFG) were used to replace river sand as fine aggregate for the production of the mortar. The TFG glass sand series mortars exhibit the worse fluidity and fluidity preservation, the shorter setting times, the lower wet density and mechanical properties than those with n-TFG glass sand. The use of TFG glass sand in the mortar also results in the lower drying shrinkage, alkali-silica reaction (ASR) expansion and leaching content of lead than the blended n-TFG glass sand mortars. Moreover, at the drying shrinkage period of 56 days, the drying shrinkage values of the mortars with TFG glass sand are within the limit of 0.075%. The mortars prepared by TFG glass sand have a low ASR expansion, at the tested age of 14 days, which are below permissible limits (0.10%). The lead leaching of the mortars with TFG glass sand comply with the regulatory limits.